Checklist of Macroalgae in Waisai Coast, Raja Ampat - Retno Suryandari; Widodo Widodo (Biology, Medicine, & Natural Product Chemistry, 2016)
Macroalgae are very abundant organisms in Indonesian coastal zone. They comprise 8.6% of the total marine organisms.The aim of the research was to identify macroalgae in Waisai Coast Raja Ampat. The results showed that 38 macroalgae were found in Waisai Coast Raja Ampat but only 29 species of macroalgae can be identified. Macroalgae found in Waisai Coast Raja Ampat are green algae, red algae and brown algae. Green algae found and identified are Caulerpa macra (Weber-van Bosse) Draisma & Prud’homme, Caulerpa racemosa var. macrophysa (Sonder wx Kutzing) W.R.Taylor,  Caulerpa sertularoides (S. Gmelin) Howe f. brevipes (J. Agardh Svedilus), Caulerpa cupressoides (Vahl) C. Agardh, Halimeda discoidea Decaisne, Halimeda Opuntia (Linnaeus) J.V. Lamoroux, Halimeda tuna (J. Ellis & Solander) J.V. Lamoroux, Halimeda cylindraceae Decaisne, Halimeda macroloba Decaisne, Avrainvillea erecta (Berkeley) A. Gepp & E.S. Gepp, Codium geppiorum O.C.Schmidt, Boergesenia forbesii (Hardvey) Feldmann, Valonia ventricosa J. Agardh, Dictyosphaeria cavernosa (Forsskål) Børgesen, Chaetomorpha spiralisOkamura, Anadyomene wrightii Harvey ex. J. E. Gray, Neomeris annulata Dickie. Red algae species found and successfully identified areAcanthophora spicifera (M. Vahl) Børgesen, Laurencia papilosa (C. Agardh) Greville, Gracilaria salicornia (C. Agardh) E.Y. Dawson, Amphiora fragilissima (Linnaeus) J.V. Lamoroux, Hypnea pannosa J. Agardh. Brown algae species  found and identified are Hormophysa cuneiformis (J.F. Gmelin) P.C. Silva, Sargassum aquifolium (Turner) C. Agardh, Sargassum polycystum C. Agardh, Turbinaria ornata (Turner) J. Agardh, Padina australis Hauck, Canistrocarpus cervicornis (Kutzing) De Paula & De Clerck Hydroclathrus clatratus (C. Agardh ) M. Howe. The only species found in Indonesia is Sargassum aquifolium.